Preferential HLA-B27 Allorecognition Displayed by Multiple Cross-Reactive Antiviral CD8+ T Cell Receptors - Rowntree, Louise C.; van den Heuvel, Heleen; Sun, Jessica; D'Orsogna, Lloyd J.; Nguyen, Thi H. O.; Claas, Frans H. J.; Rossjohn, Jamie; Kotsimbos, Tom C.; Purcell, Anthony W.; Mifsud, Nicole A. (Frontiers in Immunology, 2020)
T cells provide essential immunosurveillance to combat and eliminate infection from pathogens, yet these cells can also induce unwanted immune responses via T cell receptor (TCR) cross-reactivity, also known as heterologous immunity. Indeed, pathogen-induced TCR cross-reactivity has shown to be a common, robust and functionally potent mechanism that can trigger a spectrum of human immunopathologies associated with either transplant rejection, drug allergy and autoimmunity. Here, we report that several virus-specific CD8+ T cells directed against peptides derived from chronic viruses (EBV, CMV and HIV-1) presented by high frequency HLA-A and -B allomorphs differentially cross-react towards HLA-B27 allotypes in a highly focused and hierarchical manner. Given the commonality of cross-reactive T cells and their potential contribution to adverse outcomes in allogeneic transplants our study demonstrates that multiple antiviral T cells recognizing the same HLA allomorph could pose an extra layer of complexity for organ matching.